Multimedia development based on science technology engineering and mathematics in microbiology learning - Trio Ageng Prayitno; Nuril Hidayati (JPBIO (Jurnal Pendidikan Biologi), 2020)
Microbiology learning has not used multimedia based on science technology engineering and mathematics (M-STEM) which can help students understand the concept of microbiology and empower 21st-century skills. The purpose of this research was to develop M-STEM in microbiology learning. The research method uses research and development (R&D) with the Borg and Gall development model which consists of seven stages. The research sample was 20 students who had participated in microbiology learning and four microbiology lecturers at the department of biology education, IKIP Budi Utomo. The research instrument used a questionnaire, interview transcripts, expert validation sheets, practitioner validation sheets, and readability test sheets. The research data is the percentage of the validation score from experts, practitioners, and readability tests. The research data analysis was carried out by descriptive qualitative. The results showed that M-STEM was declared strongly valid in the aspect of media (88.36%), material (97%), usefulness in microbiology learning (99.49%), and readability (88.82%). M-STEM contains interesting features, is easy to access and operate, and the information in it is easy to understand. This research concludes that M-STEM can be recommended for use in microbiology learning. Keywords: Biology learning, microbiology, multimedia, STEM